José Martí and Human Rights - Guadarrama González, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The work discusses José Martí's main ideas on the law. It values its criteria on the human rights of certain social sectors, such as slaves and workers, as well as colonized peoples. It shows how his thinking evolved in relation to human rights. In the first stage he sometimes expressed a passive consideration of tolerance and respect, to avoid violence, as a condition of the realization of the right. His correct understanding that the Spanish government would not grant Cubans and Puerto Ricans their claimed rights led him to conclude that only by the path of revolutionary violence could these be attained. Finally, he analyses his criteria for how the right should be exercised and cultivated in the long-awaited republican life.